Contra el tiempo y el olvido: la representación del pasado traumático paraguayo en el Museo de las Memorias - Sara Sánchez del Olmo (Cahiers des Amériques Latines)
In this article, we explore the process of reconstruction and representation of Stroessner’s dictatorship in the Paraguayan public space through a concrete institution: the Museum of the Memories. Based on the analysis of its museography we want to emphasize the flaws of this space and, at the same time, to analyse the reasons that, in our opinion, prevent it from constituting a reference institution for contemporary Paraguayan society. Finally, our will is to highlight the factors that jeopardize the survival of this museum.